The Association Between Metabolic Syndrome and Characteristics of Benign Prostatic Hyperplasia: A Systematic Review and Meta-Analysis. Issue 19 (May 2016) - Wang, Jian-Ye; Fu, Yan-Yan; Kang, De-Ying
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: The purpose of this systematic review was to examine the association of metabolic syndrome (MS) with measures of benign prostatic hyperplasia (BPH) including prostate growth rate, prostate volume, International Prostate Symptom Score (IPSS), prostate-specific antigen (PSA) level, and maximal flow rate. Medline, Cochrane CENTRAL, EMBASE, CBM, and Google Scholar databases were searched until March 23, 2015 using combinations of the keywords benign prostate hyperplasia/BPH, metabolic syndrome, total prostate volume, prostate growth rate, prostate specific antigen, International Prostate Symptom Score/IPSS, maximal flow rate. Cohort or case–control studies of patients with BPH and MS that reported quantitative outcomes were included. The pooled mean differences of the outcome measures were compared between patients with and without MS. A total of 158 potentially relevant studies were identified, and 8 were included in the meta-analysis. The 8 studies included in the meta-analysis contained a total of 3093 BPH patients, wherein 1241 had MS and 1852 did not have MS. BPH patients with MS had a significantly higher prostate growth rate (pooled mean difference = 0.67 mL/y, P  < 0.001) and larger prostate volume (pooled mean difference = 6.8 mL, P  = 0.010) than the BPH patients without MS. There was no significant difference in IPSS score (pooled mean difference = 1.58, P  = 0.202) or maximal flow rate (pooled mean difference = −1.41 mL/s, P  = .345) between BPH patients with and without MS. A borderline nonsignificant difference in PSA (pooled mean difference = 0.24 ng/mL, P  = 0.056) was noted between BPH patients with and without MS. The results of this meta-analysis are consistent with literature indicating that BPH patients with MS have a higher prostate growth rate and larger prostate volume than those without MS; however, further study is necessary to determine the association of BPH and metabolic disorder elements and the potential risk of disease progression in BPH patients with MS.